Sense of coherence as a predictor of physical and psychosocial health among cardiac patients - Kocjan, Janusz (Journal of Education, Health and Sport, 2015)
Kocjan Janusz. Sense of coherence as a predictor of physical and psychosocial health among cardiac patients. Journal of Education, Health and Sport. 2015;5(6):241-250. ISSN 2391-8306. DOI 10.5281/zenodo.18558 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A241-250 https://pbn.nauka.gov.pl/works/565789 http://dx.doi.org/10.5281/zenodo.18558 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 10.06.2015. SENSE OF COHERENCE AS A PREDICTOR OF PHYSICAL AND PSYCHOSOCIAL HEALTH AMONG CARDIAC PATIENTS Janusz Kocjan Medical University of Silesia, Faculty of Medicine Summary INTRODUCTION: According to salutogenic concept, a strong sense of coherence is associated with physical and psychological health. Global life orientation is a measure of an individual’s ability to balance needs and resources of the body in confrontation with stress. AIM OF THE STUDY: The aim of the present study was to assess relationship between sense of coherence (SOC) with health-related quality of life (HRQoL), especially with physical (PC) and mental (MC) component of health in patients undergoing cardiac treatment. MATERIAL AND METHODS: 144 patients in age of 40-84 (mean age: 63,35 ± 10,71 years) were examined. The following scale were used: SOC-29 (Sense of Coherence) and SF-36 (Short Form Health Survey). Statistical analyses included perform descriptive statistics, calculate correlation between variables and comparision in groups. Levels of p<0,05 were accepted as being statistically significant values. RESULTS: The median score for SOC and its individuals components were as follows: SOC: 121,50; sense of comprehensibility: 46,00; sense of meaningfulness: 40,00; sense of manageability: 39,00. Correlation between SOC and all components with MC were noted (0,20<r<0,30; p<0,02). In case of PC, correlations were weaker (0,17<r<0,23), but statistically significant (p<0,05). Differences between group with low and strong SOC revealed in factors: physical functioning, role limitations due to physical health, pain, health-general, energy/fatigue, role limitations due to emotional problems as well as in MC and PC components (0,0000<p<0,0393). CONCLUSIONS: Sense of Coherence has an impact both for MC as well as PC. Strong SOC is associated with better HRQoL. KEY WORDS: Sense of coherence, SOC-29, health-related quality of life, cardiac patients.